Frozen Shoulder Therapy using Acupuncture - Kasan, Kasan; Priskila, Onny (Rifa'Institute, 2023)
Introduction: A frozen shoulder is a medical condition that causes pain and stiffness in the shoulder, limiting mobility and daily activities. Traditional therapy is not always effective, so acupuncture therapy is an alternative that can improve joint function and mobility. Objective: The purpose of this study was to determine the benefits of acupuncture therapy in cases of frozen shoulders. Method: The research method used is a case study with a pre-post test design. The research sample consisted of five patients with frozen shoulder. Result and Discussion: The therapy was carried out three times, and the acupuncture points used were LI 15, LI 14, SI 9, SI 10, SI 11, SI 12, and GV16. The variables observed were the level of pain and stiffness in the shoulder before and after acupuncture therapy. Conclusion: The results showed that acupuncture therapy for treating frozen shoulder showed significant changes, with an average previous VAS scale of 4.8 to 0.6, so it can be concluded that acupuncture has been proven effective as an alternative therapy for frozen shoulder cases